Pengaruh Lingkungan Kerja Dan Stres Kerja Terhadap Kinerja Pegawai Pada Balai Pelaksana Jalan Nasional Provinsi Maluku Utara - Dahlan, Fadli; Akbar, Asgar Ari (Peneliti.net, 2025)
This study aims to determine the effect of Work Environment and Job Stress on Employee Performance at the National Road Implementation Agency of North Maluku Province. The population in this study consists of 298 employees at the National Road Implementation Agency of North Maluku Province. The type of research conducted is quantitative, with a sample of 85 employees taken using the census method. The analytical method used in this study is quantitative analysis with the help of SPSS 20 software.The results of this study show that the work environment has a positive and significant effect on the performance of employees at the National Road Implementation Agency of North Maluku Province. Job stress also has a positive and significant effect on employee performance at the National Road Implementation Agency of North Maluku Province. Partial testing results found that there is a relationship between the work environment and employee performance, as well as between job stress and employee performance.